48th AIAA Aerospace Sciences Meeting Including the New Horizons Forum and Aerospace Exposition 2010
DOI: 10.2514/6.2010-323
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Leading-Edge Radius on Aerodynamic Characteristics of 50º Delta Wings

Abstract: The study focuses on the effects of the leading-edge radius on the flow over 50 o swept delta wing models. Three models were tested, one model having a sharp leading edge and the other two having a semi-circular leading edge of different radius. The vortical flow on and off the surface of the models was investigated using an oil-flow visualization and a Stereo Particle Image Velocimetry (SPIV) technique. The leading-edge radius is shown to affect the size and location of the vortices and also the vortex bursti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Over the past 70 years, the phenomenon of stationary LEVs on low aspect ratio (AR) wings has been studied extensively through analytical efforts [4,7,8], experiments [4,9,10] and numerical simulations [1113]. The most notable example of this type of wing is a delta wing, where LEV formation has been extensively studied in a variety of different settings.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past 70 years, the phenomenon of stationary LEVs on low aspect ratio (AR) wings has been studied extensively through analytical efforts [4,7,8], experiments [4,9,10] and numerical simulations [1113]. The most notable example of this type of wing is a delta wing, where LEV formation has been extensively studied in a variety of different settings.…”
Section: Introductionmentioning
confidence: 99%
“…LEVs are generated when flow separation occurs at the leading-edge region and forms a shear layer that rolls up to generate a vortex structure over the surface [4,5]; a process that commonly occurs at high angles of attack. Various experimental observations over slender delta wings have shown that these vortical structures can preserve their size and magnitude, thus becoming stationary LEVs for a wide range of flow conditions that offer significant lift enhancement [6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Because less suction is needed to reattach the separated shear layer on a thick wing, the leading-edge vortex has less strength than above a planar surface. Verhaagen investigated how the leading-edge radius variation (r le /c r ≤ 0.03) influences the vortex system and the aerodynamic characteristics of a 50 • swept delta wing [12]. He reported a decreasing distance of the vortex towards the wing's surface and the leading edge with increasing leading-edge radius.…”
Section: Introductionmentioning
confidence: 99%